Acervo De Conocimiento Frente A Los Síntomas Prodrómicos De La Psicosis Proveniente De Documentos En Español Que Reposan En Bases De Datos Digitales (2019)
A review of the literature regarding the prodromal symptoms of psychosis in various digital databases. After an introduction, categories are created with based on the documents found, in which various sections of the psychosis such as: evolution of the term, definition, types, treatment, etc. Is That is, the transformation that the term has had throughout history and how “madness” has been categorized and classified by the most influential theorists in regarding the topic.